2000
DOI: 10.1086/317457
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypogonadism among Men with Weight Loss Related to Human Immunodeficiency Virus Infection Who Were Receiving Highly Active Antiretroviral Therapy

Abstract: Previous studies have indicated that there is a significant prevalence (50%) of hypogonadism among men with acquired immunodeficiency syndrome (AIDS)-associated wasting, and for these patients testosterone administration has been shown to increase lean body mass and improve quality of life. However, the prevalence of hypogonadism is not known among men with weight loss related to human immunodeficiency virus (HIV) infection who are receiving highly active antiretroviral therapy (HAART). From 1997 through 1999,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
97
3
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(124 citation statements)
references
References 25 publications
17
97
3
7
Order By: Relevance
“…Median tPSA levels were low in our study, possibly reflecting comparatively younger age at PCa diagnosis, a higher prevalence of hypogonadism in HIV+ men (20%) [16], or an alternate biological relationship between PCa and PSA in the presence of HIV. Two American studies reported similar PSA ranges in HIV+ men to that reported here [17,18] and previous studies have shown lower latest PSA levels when PCa is present in HIV+ compared to -men prior to diagnosis [1].…”
Section: Discussioncontrasting
confidence: 59%
“…Median tPSA levels were low in our study, possibly reflecting comparatively younger age at PCa diagnosis, a higher prevalence of hypogonadism in HIV+ men (20%) [16], or an alternate biological relationship between PCa and PSA in the presence of HIV. Two American studies reported similar PSA ranges in HIV+ men to that reported here [17,18] and previous studies have shown lower latest PSA levels when PCa is present in HIV+ compared to -men prior to diagnosis [1].…”
Section: Discussioncontrasting
confidence: 59%
“…No entanto, hipogonadismo também tem sido relatado em pacientes com controle da replicação viral e dos níveis de células CD4 (19). Estudos recentes apontaram prevalência de hipogonadismo de cerca de 20% mesmo após a introdução da terapia antirretroviral altamente ativa (HAART) (20). Crum e cols.…”
Section: Disfunção Gonadal Na Infecção Pelo Hiv/aidsunclassified
“…At baseline, hypogonadism was mostly associated with low or normal gonadotropin levels, indicating a disturbance of the HPG axis. In previous studies, androgen deficiency in HIV-positive men has been associated with low CD4 cell counts, a more advanced stage of disease and weight loss [16][17][18]. In our study, cART was associated with an increase in gonadotropin levels in patients who developed lipoatrophy (P 5 0.005 for LH; P 5 0.06 for FSH), but not in negative controls (P 5 0.2 for LH; P 5 0.9 for FSH).…”
Section: Discussionmentioning
confidence: 95%